Spectroscopic Study of some Schiff Bases Derived from Dibenzoylmethane - A. Saeed, Bahjat; Al-Masoudi, Wasfi A. (JOURNAL OF ADVANCES IN CHEMISTRY, 2010)
A series of Schiff bases 7-11 derived from dibenzoylmethane have been prepared. The UV, IR, 1H NMR and mass spectra revealed theses compounds were existed mainly as the keto-enamine tautomer in the solution. The absorption bands which appeared in the range λmax = 376-406 nm were assigned to the electronic transitions which arised from the central hydrogen bonded chelated unsaturated ring system in this tautomer. The appearance of the broad singlet near d = 13 ppm due to the N-H proton and a singlet near d = 6 ppm due to the –C=C-H proton inaddition to benzoyl fragment ion signal m/z =105 in the mass spectra supported the above suggested products.